Two new species of Setostylus Matile, 1990 (Diptera: Keroplatidae) from China - Qi, Lei; Huang, Junhao; Wu, Hong; Wang, Qingyun (Zootaxa, 2022)
In this study, two new species of Setostylus (Diptera: Keroplatidae: Keroplatinae), S. tridigitus sp. n. and S. triumphus sp. n. are described, with a key to all the species of the genus. Male habitus and images of diagnostic morphological characteristics are provided. Status of these two new species is also supported by the genetic distances and neighbor-joining (NJ) tree in the DNA barcode analysis.